Handbook of Issues in Criminal Justice Reform in the United States (Cham, Switzerland: Springer, 2022)
This handbook provides a holistic and comprehensive examination of issues related to criminal justice reform in the United States from a multidisciplinary perspective. Divided into five key domains of reform in the criminal justice system, it analyzes: - Policing - Policy and sentencing - Reentry - Treatment - Alternatives to incarceration Each section provides a history and overview of the domain within the criminal justice system, followed by chapters discussing issues integral to reform. The volume emphasizes decreasing incarceration and minimizing racial, ethnic and economic inequalities. Each section ends with tangible recommendations, based on evidence-based approaches for reform. Of interest to researchers, scholars, activists and policy makers, this unique volume offers a pathway for the future of criminal justice reform in the United States.
Keywords: Criminal Justice; Manuals; Criminal Law